Sino-orbital foreign body caused by a slingshot injury in a young boy. Issue 9 (14th September 2022) - Lai, Kenneth; Laycock, Juliet; Bates, Adam; Hamann, Julian
Abstract : Slingshots or hand catapults, historically used as a military or hunting weapon, are common toys among children and young teenagers. Their use can be dangerous as a strike to the eye or orbit can result in significant injuries including blindness. We describe a rare case of a sino-orbital foreign body caused by a slingshot injury in a young boy. The case was managed by a multidisciplinary team involving ear, nose and throat, ophthalmology and paediatrics, and the foreign body of a metal ball bearing was removed using an endoscopic transnasal approach. Although the patient made a good recovery, the case highlights the danger of slingshot devices misused by children.